2010
DOI: 10.1002/chem.201000681
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic Hydrogen‐Bonded Complexes of Complementary Semiperfluorinated Components

Abstract: 2,4-Diamino-6-phenyl-1,3,5-triazines carrying one or two semiperfluorinated chains at the phenyl substituent have been investigated in binary mixtures with partially fluorinated benzoic acids by polarizing microscopy, differential scanning calorimetry, and X-ray diffraction. The number and positions of the fluorinated tails of the acid component were systematically modified. Equimolar mixtures of the triazines with the aromatic acids form discrete hydrogen-bonded heterodimers with an elongated central core. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Mixtures of 167- n with 1,3,5-triazine or with 2,4,6-triamino-1,3,5-triazine show macroscopic segregation and no LC properties. LC hydrogen-bonded complexes of substituted 2,6-diamino-1,3,5-triazines, 2,6-diamino-4-arylamino-1,3,5-triazines, and 2,4,6-triarylamino-1,3,5-triazines with semifluorinated benzoic acid derivatives have also been reported, but FT-IR measurements did not point to genuine ionic interactions in those compounds. …”
Section: Ammonium-based Ionic Liquid Crystalsmentioning
confidence: 99%
“…Mixtures of 167- n with 1,3,5-triazine or with 2,4,6-triamino-1,3,5-triazine show macroscopic segregation and no LC properties. LC hydrogen-bonded complexes of substituted 2,6-diamino-1,3,5-triazines, 2,6-diamino-4-arylamino-1,3,5-triazines, and 2,4,6-triarylamino-1,3,5-triazines with semifluorinated benzoic acid derivatives have also been reported, but FT-IR measurements did not point to genuine ionic interactions in those compounds. …”
Section: Ammonium-based Ionic Liquid Crystalsmentioning
confidence: 99%
“…Upon addition of protic solvents such as formamide, the Cub I2 phase was replaced by a lyotropic columnar mesophase. Mixtures with semiperfluorinated benzoic acids provided phase sequences of Col r and Col ob geometries. , Furthermore, H-bonded complexes of biphenyl-substituted triazines with semiperfluorinated benzoic acids formed Col h phases when two side chains are present. Mixtures displayed broader and more stable mesophases than the pure compounds. The results were rationalized by a “first-order” effect arising from the molar content of the acid component which defines the molecular geometry of the H-bonded polar central core.…”
Section: Classes Of Compoundsmentioning
confidence: 99%
“…Mixtures with semiperfluorinated benzoic acids provided phase sequences of Col r and Col ob geometries. 332,333 Furthermore, H-bonded complexes of biphenyl-substituted triazines with semiperfluorinated benzoic acids formed Col h phases when two side chains are present. 334−336 Mixtures displayed broader and more stable mesophases than the pure compounds.…”
Section: Heteroaromatic Discotic Mesogensmentioning
confidence: 99%
“…38 Mesophase behaviour of hydrogen-bonded, alkylated triazines and benzoic acids has been tuned by variation of the ratio between fluorinated and hydrogenated tails. 39, 40 An advantage of these intermolecularly hydrogen bonded systems is that with a limited number of precursors a wide variety of liquid crystalline materials are accessible. In solution, fluorinated porphyrin 41 and phthalocyanine 42 derivatives have been reported that possess potential gas or drug carrier applications.…”
Section: Introductionmentioning
confidence: 99%